2019
DOI: 10.1002/cam4.2657
|View full text |Cite
|
Sign up to set email alerts
|

Incidence rates of cardiovascular outcomes in a community‐based population of cancer patients

Abstract: Background There are limited data on the incidence of cardiovascular disease among cancer patients in the pre‐tyrosine kinase inhibitor (TKI) era. Such data are important in order to contextualize the incidence of various cardiovascular outcomes among cancer patients enrolled in clinical trials of new agents and for postmarketing surveillance. Methods A retrospective cohort study was conducted using data from the Kaiser Permanente Northern California (KPNC) population of cancer patients. The inclusion criterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
(49 reference statements)
1
1
0
1
Order By: Relevance
“…We found that the prevalence of HF was 4.0% in the study population, which was apparently higher than that in the general population in Japan over the age of 45 (approximately 1.6%) [ 16 ] and in the United States over the age of 65 (approximately 1.0%) [ 17 ]. The apparently higher prevalence of HF in patients with cancer than in the general population is consistent with a prior study that showed an HF prevalence of 7.06% after the diagnosis of various types of cancer [ 18 ]. This may be explained by several factors.…”
Section: Discussionsupporting
confidence: 90%
“…We found that the prevalence of HF was 4.0% in the study population, which was apparently higher than that in the general population in Japan over the age of 45 (approximately 1.6%) [ 16 ] and in the United States over the age of 65 (approximately 1.0%) [ 17 ]. The apparently higher prevalence of HF in patients with cancer than in the general population is consistent with a prior study that showed an HF prevalence of 7.06% after the diagnosis of various types of cancer [ 18 ]. This may be explained by several factors.…”
Section: Discussionsupporting
confidence: 90%
“…In a community-based study of 165,000 patients with cancer, the most frequent adverse outcomes were the development of heart failure, acute coronary syndrome, and diabetes ( 20 ). Several previous studies showed an increased risk for CVD among childhood cancer survivors, which was attributable largely to treatment exposures at a young age ( 8 , 21 , 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…При многих формах онкопатологий изменяются уровни таких гормонов, как инсулин и глюкагон. Это связано с тем, что опухолевые клетки получают глюкозу независимо от инсулина в ущерб другим клеткам, в том числе кардиомиоцитам [21].…”
unclassified